Effect of temperature gradient on crack initiation - Homma, H.; Shah, Qasim Hussain; Kawada, S. (Elsevier BV, 1995)
Compact tension (CT) specimens of pressure vessel steel A533B have been subjected to linear distributions of temperature along the crack line. The temperature dependence of fracture toughness for the A533B steel creates a fracture toughness gradient in such a specimen. The specimens simulated an irradiated pressure vessel wall and a functionally gradient material. The CT specimens subjected to linear distributions of temperature were tested to evaluate the fracture toughness for crack initiation. In all tests, the temperature at the crack tip was kept at -10°C or -55°C. If the value of the temperature gradient ahead of the crack tip exceeded a critical value. the fracture toughness deviated from the toughness obtained under a uniform temperature of -10°C or -55°C.